2009
DOI: 10.4067/s0717-95022009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Altered Liver Morphology and Enzymes in Streptozotocin Induced Diabetic Rats

Abstract: ZAFAR, M.; NAEEM-UL-HASSAN NAQVI, S.; AHMED, M. & KAIMKHANI, Z. A. Altered liver morphology and enzymes in streptozotocin induced diabetic rats. Int. J. Morphol., 27(3):719-725, 2009. SUMMARY:This study was undertaken to evaluate the relationship and effects of diabetes on liver morphology, architecture and function. The hepatic effects of diabetes were evaluated in vivo using streptozotocin (STZ)-induced diabetic rats as an experimental model. The degree of hepatic dysfunction was measured by using biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 44 publications
(20 reference statements)
17
68
1
Order By: Relevance
“…This blood glucose lowering effect is the result of the bioactive secondary components of the plant. Relationships between hyperglycaemia and decrease in body weight of experimental animals have been reported (Igile et al 1995;Zafar et al 2009). In this study, there was a significant (p < 0.05) decrease in body weight of the diabetic untreated group compared with the normal control and extract-treated animals ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This blood glucose lowering effect is the result of the bioactive secondary components of the plant. Relationships between hyperglycaemia and decrease in body weight of experimental animals have been reported (Igile et al 1995;Zafar et al 2009). In this study, there was a significant (p < 0.05) decrease in body weight of the diabetic untreated group compared with the normal control and extract-treated animals ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several workers have reported a significant decrease in body weight of STZ diabetic rats [43]. The reduction in the body weight of the diabetic animals could be explained on the basis of loss of structural proteins as these structural proteins contribute to body weight [44].…”
Section: Discussionmentioning
confidence: 99%
“…More so, a metabolic impairment leading to imbalance in energy can also result from impressed factors including drastic changes in environmental conditions, exposure to drugs, toxicants, pollutants and the likes [29]. Studies have shown an association between hyperglycemia and decrease in body weight of experimental animals [30]. Consequently, changes in weight are usually a fundamental index of physiological or pathological state of an experimental animal.…”
Section: Discussionmentioning
confidence: 99%